Koncepcjonowanie reform szkolnych - Muszyński, Heliodor (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
The article discusses the issue of conditions for efficient application of school reforms. Success depends not only on how it is implemented but also on its conception. The article presents the process of conception forming, which goes in 5 stages. The most important step here is the so-called technology of personreasses. The term denotes processes of personal change which the student is supposed to undergo in school.
Conceptualisation of the schoolreforms
Keywords: Koncepcja szkoły; Conception of school; Reforma edukacji; Reform of education; Szkoła; School; edukacja; education; Oświata; Learning